Correlation between serum cytokines and clinicopathological features in patients with drug-induced liver injury - Zhang, Yu; Gao, Hui; Zhang, Yu; Shao, Yue-Ming; Zhang, Rui-Hua; Wen, Xiao-Yu (Frontiers in Pharmacology, 2022)
Objectives: Changes in serum levels of cytokines have been proposed as possible biological markers of tissue damage, including drug-induced liver injury (DILI). Here, we aimed to screen cytokine markers that have guiding significance for the degree of inflammation of DILI. Patients and methods: 54 patients with DILI were retrospectively analyzed as the experimental group, and 14 healthy subjects were randomly selected as the control group. A total of 20 cytokines were detected by using a cytokine protein antibody chip, and differentially expressed proteins were screened. Results: There were significant differences in serum cytokines between DILI patients and healthy controls. Compared with the control group, the DILI group expressed 11 differential proteins. IL-8, TNF RII, TNFα, TNF RI, MIP-1β, MIP-1α and IL-1β were differentially expressed in DILI patients with different degrees of inflammation from G1 to G4. MIG, IL-12p40 and IL-10 were differentially expressed in the higher degree of inflammation groups (G2, G3 and G4 groups). Tissue inhibitor of metalloproteinases-1 (TIMP-1) was differentially expressed in the group with the highest inflammation degree (G4 group). Chemokine C-C motif ligand 1 (I-309) was only differentially expressed in the lowest inflammation group (G1 group). Conclusion: The changes and differential expression of specific cytokine levels were helpful for evaluating different degrees of inflammation of DILI.